Plasma haptoglobin as a potential biomarker for coronary artery disease in young hypertensive adults - Mohamed Bakrim, Norbaiyah; Wan Omar, Wan Fatein Nabeila; Abdullah, Aszrin; Hamidon, Nurul Nadiah; Abdul Muid, Suhaila; Badrulhisham, Aisyah (IIUM Press, 2024)
Introduction: Uncontrolled hypertension is a primary risk factor for premature coronary artery disease (CAD) in young adults. The risk of CAD among young hypertensive adults is commonly underestimated owing to the young age. Hence, identification of novel biomarker(s) to improve risk stratification of CAD in young hypertensive adults is essential for more accurate CAD risk assessment and thus to improve management of hypertension in this cohort. This study investigated plasma haptoglobin concentration in young adults with acute myocardial infarction (AMI) and hypertension to evaluate the potential of haptoglobin as a biomarker in the establishment of CAD in young hypertensive adults. Materials and Methods: A total of 120 male young adults aged between 18 to 45 years were enrolled in this cross-sectional study (40 subjects in control, hypertensive and AMI group respectively). Blood samples were collected from all subjects. Plasma concentrations of haptoglobin was measured using enzyme-linked immunosorbent assays. Other CAD risk factors including high sensitivity C-reactive protein (hs-CRP) levels were analyzed. Results: Plasma concentration of haptoglobin in the AMI group was the highest as compared to hypertensive and control group (290.63±99.90 vs. 208.47±112.93 vs. 170.02±108.11 ng/ml, p<0.006). There was a significant association between AMI and plasma haptoglobin concentration in hypertensive subjects independent of other known CAD risk factors (OR: 0.985, 95% CI 0.973-0.997, p=0.017). There was positive correlation between plasma haptoglobin and hs-CRP (r=0.0370, p<0.001). Conclusion: Plasma haptoglobin is a potential biomarker to identify young hypertensive adults who are at risk of developing CAD. (246 words)